‘Click’ Reaction in Conjunction with Diazeniumdiolate Chemistry: Developing High-Load Nitric Oxide Donors - Oladeinde, Oyebola A. (2010)
[Image: see text] The use of Cu(I)-catalyzed ‘click’ reactions of alkyne-substituted diazeniumdiolate prodrugs with bis- and tetrakisazido compounds is described. The ‘click’ reaction for the bis-azide using CuSO(4)/Na-ascorbate predominantly gave the expected bis-triazole. However, CuI/diisopropylethylamine predominantly gave uncommon triazolo-triazole products as a result of oxidative coupling. Neither set of ‘click’ condition showed evidence of compromising the integrity of the diazeniumdiolate groups. The chemistry developed has applications in the synthesis of polyvalent and dendritic nitric oxide donors.